Microglial histone H3K18 crotonylation promotes STAT1 expression and induces cognitive deficit in Alzheimer disease - Weng, Ying; He, Ting; Li, Mengzhu; Zhou, Qiuzhi; Xie, Jiazhao; Wei, Linyu; Wang, Xin; Wang, Jian-Zhi; Zhong, Maolin; Li, Shihong (Frontiers in Immunology, 2026)
BackgroundAlzheimer's disease (AD) is the most prevalent neurodegenerative disorder, yet the epigenetic mechanisms underlying its pathogenesis remain incompletely understood. Histone crotonylation, a novel post-translational modification, has been implicated in neuroinflammation. However, its role in AD-related cognitive impairment has not been elucidated.MethodsHistone crotonylation was examined in 5xFAD and Aβ42-injected mice. Crotonic acid was administered intracerebroventricular (ICV) to elevate hippocampal histone crotonylation in wild-type mice. Cognitive function was assessed using behavioral tests. Synaptic integrity was evaluated via western blotting and Golgi staining. Microglial activation and co-localization of H3K18cr were determined by immunofluorescence. Transcriptomic analysis identified differentially expressed genes and enriched pathways. The role of signal transducer and activator of transcription 1 (STAT1) was validated in BV2 microglial cells using the STAT1 inhibitor fludarabine.ResultsHippocampal pan-histone H3 crotonylation (H3Kcr) and H3K18cr were significantly upregulated in both 5xFAD and Aβ42-injected mice compared to controls. ICV injection of crotonic acid markedly elevated hippocampal H3Kcr and H3K18cr levels and induced significant cognitive deficits, shown by impaired novel object recognition and fear conditioning performance. Crotonic acid treatment resulted in synaptic dysfunction, including reduced synaptic markers (SYN1, SYT, GluA2, GluN2B) and decreased CA1 dendritic spine density. Crotonic acid also induced microgliosis with elevated Iba1 expression. H3K18cr was specifically upregulated in microglia, with no significant changes observed in neurons or astrocytes. Transcriptomic analysis identified 478 differentially expressed genes enriched predominantly in immune-related pathways, with STAT1 highlighted as a key upstream transcription factor. In BV2 cells, crotonic acid significantly increased total and phosphorylated STAT1 (Tyr701) levels via a JAK1-independent mechanism. Treatment with fludarabine effectively suppressed STAT1 expression and attenuated the production of pro-inflammatory cytokines, including TNF-α, IL-6, and IL-1β.ConclusionThis study provides the first evidence that elevated microglial H3K18cr contributes to AD-related cognitive impairment by promoting STAT1 expression and subsequent neuroinflammation. These findings identify microglial histone crotonylation as a novel epigenetic mechanism in AD pathogenesis and suggest that targeting the H3K18cr-STAT1 axis may represent a potential therapeutic strategy for AD.